Aplikasi Pengolahan Data Nilai Siswa Berbasis Data Mining Menggunakan Algoritma Naive Bayes Classifier - Setiana, Galih; Hermanto, Moch. Irwan (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
Vocational High School is a very important learning facility in Indonesia. Vocational High School is a more effective option because students will choose vocational that suits their interests and talents, with the development of vocational schools now and the progress and achievements that have been obtained, the field of expertise is now growing and growing rapidly so that it becomes the main concern of the government with the progress and some achievements in various fields produced by their students. One classification method that can be used is the Naïve Bayes algorithm. The advantage is simple but has good accuracy. Based on the results of the experiment, this method is proven to be used effectively for us to make the classification of news automatically with good accuracy and have a relatively simple calculation, in addition to the creation of applications that is by using Visual Basic. The study produced a classification report along with supporting applications. In this study, it is known that data patterns and some assessment variables that can produce a certain class that can be used in terms of determining student graduation in a good and effective way that can help teachers' performance in managing student value data well